BPJS Verification Pending Claim Case Accuracy Diagnostic Codes Inpatients - Mandia, Sayati (Jurnal Kesehatan - STIKes Prima Nusantara, 2023)
Background: The process of submitting claims for BPJS (Badan Penyelenggara Jaminan Sosial) under the INA-CBGs (Indonesian Case-Based Groups) program is contingent upon the utilization of the ICD-10 (International Classification of Diseases, Tenth Revision) code. The delay in BPJS claims can be attributed to problems in the ICD-10 coding process conducted by the Casemix coding team.Objective: The objective of this research is to assess the precision of coding pending claims.Methodology: The chosen research methodology is descriptive in nature, employing a quantitative approach. The research employed the Simple Random Sampling approach for the purpose of sampling. The gathering of research data was conducted through the method of direct observation of pending claim documents. The study was carried out in the Casemix Unit of RSU Aisyiyah Padang. The study encompasses the entirety of claim files from January to June 2022, constituting the research population. A sample size of 94 papers has been selected for analysis. The process of data analysis encompassed descriptive, graphical, and inferential methods in order to present a comprehensive understanding of coding errors.Result: The findings indicate that a total of 29 documents, accounting for about 30.85% of the total, had delays throughout the period of January to June 2022 as a result of inaccuracies related to ICD-10 diagnostic codes. The number of pending inpatient claims reached its peak in January, with a total of 25 cases, of which 11 were attributed to code problems. The majority of the current claim cases are concentrated in Block E, which pertains to coding for endocrine, nutritional, and metabolic illnesses.Conclusion: In conclusion, the suspension of BPJS claims at RSU is influenced by the accuracy of diagnostic coding that is based on ICD-10.